Chestnut-like copper cobalt phosphide catalyst for all-pH hydrogen evolution reaction and alkaline water electrolysis. Issue 23 (31st May 2019) - Yan, Liang; Zhang, Bing; Zhu, Junlu; Zhao, Shanzhi; Li, Yunyong; Zhang, Bao; Jiang, Jianjun; Ji, Xiao; Zhang, Haiyan; Shen, Pei Kang
Abstract : Novel chestnut-like Cu x Co1− x P/CP exhibited excellent activities for the HER at all pH values and the OER in alkaline solution. Abstract : A novel type of chestnut-like copper cobalt phosphide (Cu x Co1− x P) nanoarray on carbon fiber paper (CP) for the splitting of water was synthesized through a simple hydrothermal reaction followed by in situ phosphorization treatment. As a hydrogen evolution reaction (HER) catalyst, Cu x Co1− x P/CP showed high HER activity at all pH values. To drive a current density of 10 mA cm −2, the optimized Cu0.075 Co0.925 P/CP required an overpotential of 47, 120, and 70 mV in acidic, neutral, and alkaline media, respectively. In addition, Cu0.075 Co0.925 P/CP exhibited excellent activity for the oxygen evolution reaction (OER) with a small overpotential of 221 mV to reach 10 mA cm −2 . Furthermore, when Cu0.075 Co0.925 P/CP was used as both the cathode and anode for overall water splitting in 1.0 M KOH, the two-electrode electrolyzer only needed a cell voltage of 1.55 V to achieve 10 mA cm −2, which is superior to that of the noble metal-based Pt/C‖IrO2 cell and most previously reported electrocatalysts. Moreover, this electrolyzer could be powered by a single AA battery with a voltage of 1.5 V. Density functional theory (DFT) calculations further proved that the good catalytic activity of Cu x Co1− x P/CP resulted from its smaller hydrogen adsorption free energy (Δ G H* ) and overpotential. This work provides a promising strategy to design high-performance and low-cost electrocatalysts for overall water splitting and other energy-related applications.